ICT enabled Technologies issues in implementation (especially in perspective of Uttrakhand Rural Areas) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
Information Communication & Technology makes the entire world a Global Village. The high speed connectivity, communication and technology are turn out to be a magic wand for the human progress and prosperity. But it looks so that this progress is confined with the virtual villages like metros and cities. The semi urban and villages looks far behind from the actuality i.e. implementation of ICT. This Paper is not a critic on the Government efforts. It is merely a survey report to put a thought on the efforts inadequacy, unable to reach up to grass root level. The current study will provide a microscopic view of the ground reality of villages especially in Hardwar district and show reasons why implementation of ICT is not effective over there. The probable solution of implementation of ICT is also worked out in the end.